2023
DOI: 10.3390/app13042192
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Sulfate Metabolites of Chlorogenic Acid

Abstract: This study aimed to determine the antioxidant properties of the sulfate monoesters of ferulic, caffeic, dihydroferulic and dihydrocaffeic acids, the main metabolites of chlorogenic acids. These compounds are not commercially available, so they were synthesized in the laboratory. The LC-MS/MS analysis allowed for the full characterization of these derivatives, which has made them reliable standards for further research. Purified metabolites including ferulic acid-4-O-sulfate, caffeic acid-4-O-sulfate and caffei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the case of dihydrocaffeic acid, as well as other phenolic acids used in the study, it was observed that sulfation of the hydroxyl group in the aromatic ring caused a significant reduction in antioxidant activity. Comparing DHCA to its monosulfate derivative (mixture of both sulfates at an unknown ratio), the authors obtained the following results: (a) in the CUPRAC method, 0.49 mM of Trolox equivalents (TE) for DHCA, and no activity for monosulfates; (b) using Folin-Ciocalteu assay, 72.07 to 2.19 ppm of gallic acid equivalents; (c) in the DPPH radical test, 0.563 mM of TE (39.96% of scavenging effect), which was approximately 10 times higher than the values for monosulfates (0.051 mM and 3.61%) [84].…”
Section: Antioxidant Activitymentioning
confidence: 90%
See 2 more Smart Citations
“…In the case of dihydrocaffeic acid, as well as other phenolic acids used in the study, it was observed that sulfation of the hydroxyl group in the aromatic ring caused a significant reduction in antioxidant activity. Comparing DHCA to its monosulfate derivative (mixture of both sulfates at an unknown ratio), the authors obtained the following results: (a) in the CUPRAC method, 0.49 mM of Trolox equivalents (TE) for DHCA, and no activity for monosulfates; (b) using Folin-Ciocalteu assay, 72.07 to 2.19 ppm of gallic acid equivalents; (c) in the DPPH radical test, 0.563 mM of TE (39.96% of scavenging effect), which was approximately 10 times higher than the values for monosulfates (0.051 mM and 3.61%) [84].…”
Section: Antioxidant Activitymentioning
confidence: 90%
“…The most common antioxidant assays are based on simple chemical reactions between an antioxidant and model free radicals such as 2,2-diphenyl-1-picrylhydrazyl radical (DPPH • ) or the radical cation of 2,2 -Azino-bis(3ethylbenzothiazoline-6-sulfonic acid) diammonium salt (ABTS +• ), or on metal ions, as in FRAP (Ferric Reducing Antioxidant Power) and CUPRAC (CUPric Reducing Antioxidant Capacity) methods. As well, in the case of dihydrocaffeic acid and its derivatives, these tests were successfully used [1,5,25,26,[81][82][83][84].…”
Section: Antioxidant Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Ali et al established a precise and eco-friendly approach for the determination of a novel TKI (erdafitinib) in human plasma samples through a validated UPLC-MS/MS method, and the developed assay was further applied in metabolic stability studies [5]. Rogozinska et al investigated the antioxidant activity of the main metabolites of chlorogenic acid (ferulic, caffeic, dihydroferulic, and dihydrocaffeic acids) by synthesizing them in the laboratory, and they were characterized via LC-MS/MS analysis [6]. Sobolewska et al reported a post-column derivative HPLC-based fluorescence detection method for the quantitative analysis of a new boronic acid derivative, which is clinically developed as an anticancer agent [7].…”
mentioning
confidence: 99%